Effects of time of day on power output and thermoregulation responses during cycling over a simulated hilly course in the heat (35C) - Bardis, K.; Atkinson, G. (Biology of Exercise, 2008)
The aim of the present investigation was to compare responses to sustained exercise in the morning and evening in the heat (35°C) over a hilly prolonged simulated course. The thermoregulatory response examined was core temperature (Tc). In addition power output, and time were examined. Eight active males (25 -40 years) were instructed to work as hard as possible over the entire exercise period, with variation of pedal frequency permitted at any time. Two prolonged sessions were performed at 08:00 and 17:00 h, and counterbalanced with at least 5 days recovery between tests. The examined variables showed no significant main effect for time of day. Mean power output in the evening was greater by 9 Watts (W) in comparison to the morning exercise. Furthermore, time increased by 2.8% in the evening compared to the morning. Future studies should include the examination of circadian rhythms and performance during undulating courses using each grat period.